2015
DOI: 10.1309/ajcp2n1afxefovye
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Distinction of Primary Sweat Gland Carcinoma and Metastatic Breast Carcinoma

Abstract: These data suggest that p63 and CK5/6 are specific determinants for sweat gland carcinoma in the stated setting. In the absence of those analytes, metastatic breast carcinoma cannot always be identified to the exclusion of a primary tumor. This diagnostic scenario continues to require the procurement of a detailed clinical history regarding the number and duration of skin lesions in any given case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 28 publications
0
41
1
1
Order By: Relevance
“…One of the invasive adenocarcinomas in vulvar type Ic EMPDs in our study was an eccrine carcinoma. Cutaneous eccrine carcinomas were positive for GATA3 in 36% to 68% cases [68, 69]. The only eccrine carcinoma in our study showed 4+ GATA3 staining (>75% cells).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…One of the invasive adenocarcinomas in vulvar type Ic EMPDs in our study was an eccrine carcinoma. Cutaneous eccrine carcinomas were positive for GATA3 in 36% to 68% cases [68, 69]. The only eccrine carcinoma in our study showed 4+ GATA3 staining (>75% cells).…”
Section: Discussionmentioning
confidence: 53%
“…Their distinction relies on morphology and other markers such as p63 and GCDFP15. Eccrine carcinomas were often positive p63 (85% to 89%) whereas primary type Ib EMPDs were not [68, 69]. Eccrine carcinomas were only rarely positive for GCDFP15 (5%) [69].…”
Section: Discussionmentioning
confidence: 99%
“…The most useful histological features supporting a diagnosis of SMBC rather than primary cutaneous SGC are location of the tumor in the deep dermis or subcutaneous tissue, multifocality and lymphovascular invasion, but these features are not always entirely reliable . Making a differential diagnosis between SGC and SMBC is usually difficult to impossible based on morphological analysis of hematoxylin–eosin (HE)‐stained specimens alone . This is not surprising because the breast and the sweat glands, especially apocrine glands, are functional and structural homologs.…”
Section: Sweat Gland Neoplasmsmentioning
confidence: 99%
“…However, these antibodies are usually also positive in benign and malignant sweat gland tumors, and thus fail to distinguish SMBC with high sensitivity and specificity. Recently, other antibodies have been examined for this purpose, including anti‐p63, cytokeratin (CK)5/6, podoplanin (D2‐40) and mammaglobin (MMG) antibody …”
Section: Sweat Gland Neoplasmsmentioning
confidence: 99%
“…Importantly, ER and PR are often negative in higher-grade breast cancers and rare morphologic variants. In such cases, a panel including p63, CK5/6 and D2-40 reportedly helps differentiate breast and adnexal neoplasia, although these stains are not entirely specific [39,40,41]. …”
Section: Discussionmentioning
confidence: 99%